2016
DOI: 10.1097/01.prs.0000475754.71333.f6
|View full text |Cite
|
Sign up to set email alerts
|

Full Facial Feminization Surgery

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 20 publications
6
66
1
2
Order By: Relevance
“…I recommend a top-to-down approach in FFS procedures as the swelling reduces in a top-to-down manner due to gravity. This is contrary to the article by Raffaini et al, 25 who recommend a down-to-up approach.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…I recommend a top-to-down approach in FFS procedures as the swelling reduces in a top-to-down manner due to gravity. This is contrary to the article by Raffaini et al, 25 who recommend a down-to-up approach.…”
Section: Discussioncontrasting
confidence: 66%
“…Most of the current publications 10 17 25 26 have reported complete FFS as a single surgery. This involves 8 to 9 hours of surgery under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a validated QoL survey (SF-36v2), Ainsworth and Spiegel 1 found that transwomen without gender reassignment surgery or FFS had lower physical-, social-, and mental health-related QoL compared with the general female population, while the mental health QoL of transwomen after gender reassignment surgery, FFS, or both, was similar to the general population. These findings have since been corroborated by two follow-up studies 41 42 .…”
Section: Postoperative Outcomesmentioning
confidence: 53%
“…It is frequently used with other facial surgical procedures owing to many reasons, such as its easy application, low cost, and high patient satisfaction. Furthermore, it is becoming more and more important in facial feminization surgeries (17). The evaluation stage of the patients, the treatment plan, the surgical procedure to be performed, the possible complications, and the patient's followup are current issues for mentoplasty.…”
Section: Discussionmentioning
confidence: 99%